Polyomavirus large T antigens: Unraveling a complex interactome - Matthew R. Googins; Ping An; Christian H. Gauthier; James M. Pipas (Tumour Virus Research)
All members of the polyomavirus family encode a large T antigen (LT) protein that plays essential roles in viral DNA replication, regulation of viral gene expression, and the manipulation of numerous cellular pathways. Over 100 polyomaviruses have been discovered in hosts ranging from arthropods and fish to mammals, including fourteen that infect humans. LT is among the most studied viral proteins with thousands of articles describing its functions in viral productive infection and tumorigenesis. However, nearly all knowledge of LT activities is based on the studies of simian virus 40 (SV40) and a few other viruses. Comparative studies of LT proteins of different polyomaviruses have revealed a remarkable diversity in the mechanisms by which LT proteins function across different polyomavirus species. This review focuses on human polyomaviruses highlights the similarities and differences between polyomavirus LTs and highlights gaps in our understanding of this protein family. The concentration of knowledge around SV40 LT and the corresponding lack of mechanistic studies on LT proteins encoded by other human and animal polyomaviruses severely constrains our understanding of the biology of this important virus family.